Micromelanomas: A Review of Melanomas ≤2 mm and a Case Report - Sharad P. Paul (Case Reports in Oncological Medicine)
The ABCD acronym used to screen pigmented lesions for melanoma obviously was not designed to contend with melanomas that are under 2 mm in diameter. Previously, views ranged that such small lesions could not be melanomas until a few reports of such “micromelanomas” emerged. The author presents a 2 mm melanoma in situ presenting as an insignificant pigmented lesion in a 60-year-old patient with no previous history of melanoma or multiple nevi—which is usually the norm in cases of small melanoma. This paper reiterates the fact that when it comes to a melanoma, size does not matter. In this paper, the term “micromelanoma” is used by the author to represent melanomas under 2 mm. Dermatoscopy and histopathology findings are discussed in this case, along with a review of small melanomas.